2008
DOI: 10.1038/bjp.2008.355
|View full text |Cite
|
Sign up to set email alerts
|

Central muscarinic receptor subtypes involved in pilocarpine‐induced salivation, hypertension and water intake

Abstract: Background and purpose: Recent evidence has suggested that pilocarpine (ACh receptor agonist) injected peripherally may act centrally producing salivation and hypertension. In this study, we investigated the effects of specific M 1 (pirenzepine), M 2 /M 4 (methoctramine), M 1 /M 3 (4-DAMP) and M 4 (tropicamide) muscarinic receptor subtype antagonists injected into the lateral cerebral ventricle (LV) on salivation, water intake and pressor responses to peripheral pilocarpine. Experimental approach: Male Holtzma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
1
10
1
1
Order By: Relevance
“…Recently, pharmacological studies have shown that forebrain lesions or intraventricular injection of atropine reduced pilocarpine-induced salivation, indicating central mechanism of salivary secretion (Takakakura et al 2003;Lopes de Almeida et al 2006). In addition Borella et al (2008) have demonstrated central M 3 receptors to be involved in pilocalpine-induced salivation. Therefore, the extensive distribution of oxybutynin in the CNS might lead to peripheral adverse effects such as dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pharmacological studies have shown that forebrain lesions or intraventricular injection of atropine reduced pilocarpine-induced salivation, indicating central mechanism of salivary secretion (Takakakura et al 2003;Lopes de Almeida et al 2006). In addition Borella et al (2008) have demonstrated central M 3 receptors to be involved in pilocalpine-induced salivation. Therefore, the extensive distribution of oxybutynin in the CNS might lead to peripheral adverse effects such as dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…water intake induced by pilocarpine i.p. depends on activation of central muscarinic receptors (Borella et al, 2008). A difference is that rats treated with carbachol i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…The doses of the drugs used were based on previous studies that injected these drugs central or peripherally (Camargo et al, 1984(Camargo et al, , 2009Menani et al, , 2000Andrade et al, 2004;Borella et al, 2008).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides activation of the glandular muscarinic receptors, pilocarpine activates muscarinic receptors in the central nervous system. 26 The central activation could of course lead to stimulation of the salivary glands from both divisions of the autonomic nervous system. By this it follows that the composition of pilocarpine-induced saliva does not exclusively reflects a salivary response of the parasympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%